Impact of population ageing on the application of industrial robots: Evidence from China - Zhao, Yantong; Said, Rusmawati; Ismail, Normaz Wana; Haris, Asmaddy; Hamzah, Hanny Zurina (Elsevier, 2024)
China is experiencing a rise in its ageing population alongside rapid advancements in industrial robotics. Using panel data from China's industries (2006 to 2021), this study empirically examines the impact of population ageing on the application of industrial robots. The results show that population ageing significantly promotes industrial robot application. The impact of population ageing on the application of industrial robots varies by industry. The promotion effect is greater in low and medium-technology industries than that of high-tech industries. This effect became more evident after 2012. Industries with high state ownership exhibit stronger influence coefficients than those with lower state ownership. Mechanism analysis indicates that population ageing promotes industrial robot adoption through the labour cost substitution effect. These findings offer insights for government policies to promote sustainable ageing and upgrading the manufacturing sector through artificial intelligence represented by the application of robotics. © 2024 Elsevier B.V.